Prevalence and associated factors of premenstrual dysphoric disorder among high school students in Finote Selam town, northwest Ethiopia - Kibralew, Getasew; Demilew, Demeke; Koye, Selam; Yitayih, Sewbesew; Kelebie, Mulualem; Melkam, Mamaru; Tadesse, Gebresilassie; Fentahun, Setegn; Nakie, Girum; Wassie, Yilkal Abebaw; Amare, Tadele (Frontiers in Psychiatry, 2024)
Background Premenstrual dysphoric disorder (PMDD) is the most prevalent but neglected psychiatric disorder, with somatic symptoms that are severe enough to markedly affect usual daily activities and have a negative impact on mental health and quality of life by affecting female patients’ behavior and cognition. Studies regarding premenstrual dysphoric disorder and associated factors among high school students in low- and middle-income countries are limited. Therefore, the aim of this study was to assess the prevalence and associated factors of PMDD among high school students, and this is pivotal in further investigation. Methods A school-based cross-sectional study was conducted from March 25 to April 17, 2023 using a simple random-sampling technique to select a sample of 564 participants. Premenstrual dysphoric disorder was assessed using the Diagnostic and Statistical Manual of Mental Disorders (DSM-5). Self-administered standardized questionnaires were used to collect data. Result A total of 548 study participants participated, with a 97.2% response rate. The prevalence of premenstrual dysphoric disorder among high school students was found to be 33.03% (95%CI: 29.20–37.09). In a multivariable analysis, irregular menstruation cycle (AOR = 4.242, 95%CI = 2.182–8.246), depression (AOR = 5.272, 95%CI = 2.779–10.002), having greater than 4 days of menstruation bleeding duration (AOR = 2.138, 95%CI = 1.105–4.138), and high perceived stress (AOR = 3.468, 95%CL = 1.217–9.880) were the factors significantly associated with premenstrual dysphoric disorder. Conclusion The overall prevalence of PMDD which was one-third among high school students was high. Moreover, long duration of menstruation bleeding, depressive symptoms, irregular menstruation cycle, and high perceived stress were significant factors in PMDD. Therefore, it needs early screening and intervention in primary healthcare settings, especially for those who have high perceived stress, having depression, having a long duration of menstruation bleeding, and having an irregular menstruation cycle, so as to have good academic achievement and psychological wellbeing.